Artificial intelligence : thinking machines and smart robots with science activities for kids - Smibert, Angie ("Build it yourself" series., 2018)
Introduces teens to the history, development, and uses of artificial intelligence through hands-on STEM activities. Includes primary sources, a timeline, QR codes, discussion questions, sidebars, fact boxes, color photographs and illustrations, a glossary, and further resources.